Contemporary Painting - Vogt, Paul (New York : Harry N. Abrams Inc. Publishers, 1981)
Matta Echaurren, Roberto ; Gorky, Arshile ; De Kooning, Willem ; Motherwell, Robert ; Pollock, Jackson ; Kline, Franz ; Rothko, Mark ; Newman, Barnett ; Still, Clyfford ; Francis, Sam ; Tobey, Mark ; Twombly, Cy ; Bacon, Francis ; etc.
Engels
boek